PERANCANGAN DAN PEMBUATAN GAME “WISATA MASA DEPAN (WEMADE)” MENGGUNAKAN METODE MDLC (MULTIMEDIA DEVELOPMENT LIFE CYCLE) - Shabian Arsyl Yonanta; Moch Yogi Firmansyah; Dita Aulia Oktavian; Diana Novita Sari; Amalia Ramadhani Amanda; Dodik Arwin Dermawan (JURNAL TEKNIK INFORMATIKA INOVATIF WIRA WACANA, 2022)
Surabaya and Yogyakarta are cities on the island of Java that have the potential for attractive tourist objects to be visited by tourists, so that they can generate income for the economic development of the two cities. However, there are some people today who still do not know what tourist attractions are in the city, due to lack of knowledge. To grow knowledge about tourism objects, promotion strategies from various media are needed, one of which is through game media. The development of technology now, games are not only as a means of entertainment but also as a means of education. The development of the desktop-based "WeMade" game application is used as a promotional medium to introduce the beauty of tourist attractions in the cities of Surabaya and Yogyakarta, besides that there is a quiz as a differentiator between the WeMaDe game and other games. In the design and manufacture of this game, using Game Engine Unity with the theme of tourist attractions in the city of Surabaya and Yogyakarta. The methodology used in the design and manufacture of this game is the Multimedia Development Life Cycle (MDLC) method.